Performance assessment innovations for elite snowboarding - Harding, J. W.; James, D. A. (Procedia Engineering, 2010)
This paper provides a review of objective performance assessment in elite half-pipe snowboarding. Half-pipe snowboarding is currently coached and judged in competition using subjective measures. Like other sports that rely on subjectivity however, the methodology underpinning how coaches assess athletic progression and judges score performance is open for debate. This paper focuses on technology assisted, objective performance assessment. Key considerations are the specificity of the information, the accuracy and reliability of results, the processing time required and the current accessibility.